Monitoring temperature effects on flax cell-wall mechanical properties within a composite material using AFM. (August 2018) - Siniscalco, David; Arnould, Olivier; Bourmaud, Alain; Le Duigou, Antoine; Baley, Christophe
Abstract: PeakForce Quantitative Nano-Mechanical property mapping (PF-QNM) was applied to explore the nano-mechanical properties of the cell wall of two kinds of flax fibre preparation: isolated and within a poly-(butylene succinate) (PBS) or maleic anhydride grafted poly-(propylene) (PP-MAPP) matrix in unidirectional flax (UD) composites. Isolated flax fibres were subjected to a thermal cycle of 8 min from ambient temperature to 250 °C. At the same time, flax fibres in a matrix were subjected to an identical cycle from 140 °C to 250 °C, depending on the nature of the matrix. At the macroscopic scale, tensile tests on both types of sample preparation showed the same trends in temperature effects on the mechanical properties. At the cell wall scale, although no gradient in the cell-wall indentation modulus was revealed by PF-QNM for isolated fibres, a very slight global loss was observed above 210 °C, in accordance with the literature. This decrease was more pronounced for flax fibres within a matrix due the confinement effect of the polymer matrix which isolates fibres from the external environment during thermal treatment. The evolution of the mechanical behaviour of the cell walls leads to embrittlement of the UD composite, underlining the importance of time-temperature couple monitoring during the processing of plant fibre composites. Highlights: AFM mechanical measurements are performed on flax cell walls after thermal treatment. A significant decrease in cell-wall stiffness is highlighted above 210 °C. The stiffness drop is enhanced in polymer-embedded fibres compared to isolated fibres. No mechanical gradient is found on fibre sections after thermal exposure. Interestingly, a similar trends are highlighted at the cell-wall and composite scale.